Factors Affecting Employees’ Intention to Adopt Artificial Intelligence Systems: An Applied Study on The Communication Sector - Zayed, Adel M.; Nasr, Ragaa (The Arab Journal of Administration, 2024)
Objective: This research aims to study and analyze the factors influencing the intention of employees to adopt artificial intelligence (AI) in the Egyptian telecommunications sector. Research is particularly important in the modern era where AI has become an essential element of achieving the competitive advantage of organizations. Design/Methodology: The descriptive approach was relied upon. Of these, 384 questionnaires were distributed, of which 350 were subjected to statistical analysis by 91%. Considering the research problem and by integrating the elements of a model (Unified Theory of Technology Acceptance (UTAUT) and the Theory of Acceptance of Technology (TAM), four hypotheses were formulated to test the expected relationships, and the data were analyzed based on statistical programs (SPSS&AMOS) through a certain set of statistical tests. Results: The results of the research were the acceptance of the four hypotheses of the research, which are H.1: Expected performance has a statistically significant positive effect (0.542) on the intention of employees to adopt artificial intelligence. H.2: The expected effort has a statistically significant positive effect (0.525) on the intention of employees to adopt artificial intelligence. H.3: Perceived risks have a statistically significant negative impact (0.580-) on the intention of employees to adopt AI. H.4: Supportive conditions have a statistically significant positive impact (0.549) on the intention of employees to adopt AI. The researchers made a set of recommendations to help managers of the researched companies in supporting employees to ensure they accept adopting artificial intelligence.